Graphene based Web Framework for Energy Efficient IoT Applications (Journal of Information Technology and Digital World, 2021)
Energy efficiency is a crucial factor to be considered while designing sensor network based Internet of Things (IoT) applications due to the compromise in terms of power constraint in these devices. The overall network and IoT device lifetime may be increased significantly by enhancing the energy conservation schemes. Design changes, duty cycle optimization at the MAC layer and various other solutions are proposed to achieve efficiency in energy utilization. In IoT sensing applications based on cloud computing, these challenges are overcome by means of integrating the constrained application mechanism with abstraction layer as proposed in this paper. The round trips for graph-based data representation and data delivery are reduced by incorporating the cloud services with an efficient web framework in order to achieve efficient data management and energy conservation in the IoT sensing applications. In specific applications, the aforementioned objectives may be achieved by the integration of potential technologies. Google cloud services along with Graphene web framework, RIOT OS and Z1 IoT motes are used for developing a testbed in the constrained applications at the abstraction layer for interfacing the proposed implementation. The sensor networks in IoT applications have achieved significant reduction in energy consumption and delay of data delivery using the proposed method when compared to the existing baseline approaches.
Keywords: Wireless sensor networks; Internet of things; Abstraction layer; Graphene